2020
DOI: 10.1186/s40623-020-01310-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface deformation evolution in the Pearl River Delta between 2006 and 2011 derived from the ALOS1/PALSAR images

Abstract: This study monitors the land subsidence of the whole Pearl River Delta (PRD) (area: ~ 40,000 km2) in China using the ALOS1/PALSAR data (2006–2011) through the SBAS-InSAR method. We also analyze the relationship between the subsidence and the coastline change, river distribution, geological structure as well as the local terrain. The results show that (1) the land subsidence with the average velocity of 50 mm/year occurred in the low elevation area in the front part of the delta and the coastal area, and the ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…However, the areas with more pronounced deformation in the results align with the spatial distribution of factors such as the thickness of the soft soil layer, the intensity of groundwater extraction, and the density of buildings. Overall, the magnitude and spatial distribution of ground deformation in Zhuhai obtained in this study for the years 2020-2021 are consistent with the historical deformation patterns in Zhuhai observed by previous researchers for the years 2006-2011 [11,63] and 2015-2020 [5,10,49]. The maximum sedimentation rate, as reported in previous studies [10,11,49], is consistently observed in the reclaimed area of Zhuhai, specifically in the Gaolan Port area (Area C), which aligns with the findings of this study.…”
Section: Results Of Ground Deformation In Zhuhaisupporting
confidence: 91%
“…However, the areas with more pronounced deformation in the results align with the spatial distribution of factors such as the thickness of the soft soil layer, the intensity of groundwater extraction, and the density of buildings. Overall, the magnitude and spatial distribution of ground deformation in Zhuhai obtained in this study for the years 2020-2021 are consistent with the historical deformation patterns in Zhuhai observed by previous researchers for the years 2006-2011 [11,63] and 2015-2020 [5,10,49]. The maximum sedimentation rate, as reported in previous studies [10,11,49], is consistently observed in the reclaimed area of Zhuhai, specifically in the Gaolan Port area (Area C), which aligns with the findings of this study.…”
Section: Results Of Ground Deformation In Zhuhaisupporting
confidence: 91%
“…Additionally, Dongguan City is an important economic city in China, so human activities are frequent, such as engineering construction, factory operations, and groundwater extraction. These factors, together, contribute to the continuous subsidence [12,48], which deserve timely monitoring.…”
Section: Deformation Extraction Results Of Dongguan Citymentioning
confidence: 99%
“…In this paper, surface activity is defined as the cumulative duration of ground motion and can provide the basis for a quantitative and qualitative analysis of land subsidence and its influencing factors. It is believed that surface activity can also provide preparatory information for the subsequent prediction and early warning of geological hazards such as land subsidence [50].…”
Section: Surface Activitymentioning
confidence: 99%